93 The use of in situ simulation to support local governance processes. (17th November 2016) - Wilding, D; Meredith, G
Abstract : Objectives: Simulation in situ is increasingly recognised as a valuable tool for multidisciplinary team training, providing opportunity for review of both technical and non-technical skills. It is also recognised to have a role in the detection of latent safety threats (LSTs). We aimed to develop and implement a pathway for reporting LSTs which can be used to support local governance. Methods: In 2014/2015, our simulation team developed a formal reporting pathway to highlight LSTs identified during simulation training. The pathway was implemented in April 2015 and reporting and responses were reviewed after six months Results: Between April and September 2015 the simulation team provided 61 in situ simulation training sessions within the local trust. 21 sessions (34%) resulted in provision of reports identifying LSTs, with a total of 30 LSTs identified. Following reporting, responses to 25 of the 30 identified LSTs were received. This produced either an immediate change to working practice (12 of 25) or escalation of the threat to senior clinical staff and governance teams for review (13 of 25). Conclusions: Following implementation of a reporting pathway, we have been able to demonstrate that simulation has a positive role in the detection and mitigation of LSTs. Formal reporting can provide information to support departmental governance processes.